FUNGSI SIDIK JARI DALAM PENGUNGKAPAN KASUS TINDAK PIDANA PEMBUNUHAN (Studi Kasus pada Ditreskrimum Polda Sulawesi Selatan) - Winda, Tri Wulandari; Renggong, Ruslan; Siku, Abdul Salam (Postgraduate Bosowa University Publishing, 2019)
The purpose of this study was to find out the Fingerprint Function for investigators in disclosing criminal cases of murder and barriers experienced by investigators in conducting evidence with Fingerprint (Dactyloscopy) at the South Sulawesi Regional Police Regional Police Directorate. This study uses a type of qualitative research, by examining and studying a science of fingerprint identification which is used as the basis for conducting problem solving and qualitative analysis. The results of the research are: fingerprint function for investigators in disclosing criminal cases of murder which states that by identifying or observing fingerprints, one can find out one's identity in detail and clearly because as we know in this world no one has a fingerprint. the same so that the fingerprints possessed by humans are not the same and the obstacles of investigators in conducting evidence with the science of fingerprinting, ie the crime scene is no longer in the status quo or the crime scene is damaged so investigators have difficulty identifying fingerprints. This can be seen by the existence of criminal cases of murder in the South Sulawesi Regional Police Headquarters Ditreskrimum